Amnioreduction in a singleton pregnancy: A systematic review. (November 2013) - Thompson, A.; Mone, F.; McComiskey, M.; Ong, S.
Abstract : The aim of this study was to investigate the risk of adverse events following amnioreduction in a singleton pregnancy. A systematic review was conducted. Literature was identified by searching two bibliographical databases between 1991 and 2011, without language restrictions. The data extracted and overall rates and confidence intervals for each adverse event were calculated. Four studies met the selection criteria for systematic review. The rate of symptom relief in one study was 100%. Because of the small numbers and wide confidence intervals, an exact quantification of risk of adverse events cannot be determined.